2018
DOI: 10.3389/fphar.2018.00804
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Non-radioactive Assessment of mGlu5 Receptor-Activated Polyphosphoinositide Hydrolysis in Response to Systemic Administration of a Positive Allosteric Modulator

Abstract: mGlu5 receptor-mediated polyphosphoinositide (PI) hydrolysis is classically measured by determining the amount of radioactivity incorporated in inositolmonophosphate (InsP) after labeling of membrane phospholipids with radioactive inositol. Although this method is historically linked to the study of mGlu receptors, it is inappropriate for the assessment of mGlu5 receptor signaling in vivo. Using a new ELISA kit we showed that systemic treatment with the selective positive allosteric modulator (PAM) of mGlu5 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Moreover, new studies using mGluR5‐mediated polyphosphoinositide (PI) hydrolysis functional assays in mice demonstrated that systemic administration (i.p.) of VU0360172‐stimulated PI hydrolysis at a dose of 30 mg/kg in hippocampus, striatum, and prefrontal cortex (Zuena et al, 2018). Previously we demonstrated that in addition to suppressing post‐traumatic neurotoxic neuroinflammation, VuPAM treatment also up‐regulates an anti‐inflammatory microglial phenotype in the injured cortex, whereas an mGluR5 orthosteric agonist does not (Loane et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new studies using mGluR5‐mediated polyphosphoinositide (PI) hydrolysis functional assays in mice demonstrated that systemic administration (i.p.) of VU0360172‐stimulated PI hydrolysis at a dose of 30 mg/kg in hippocampus, striatum, and prefrontal cortex (Zuena et al, 2018). Previously we demonstrated that in addition to suppressing post‐traumatic neurotoxic neuroinflammation, VuPAM treatment also up‐regulates an anti‐inflammatory microglial phenotype in the injured cortex, whereas an mGluR5 orthosteric agonist does not (Loane et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…mGlu5 has a close partnership with the NMDARs in terms of regulating synaptic plasticity (Zuena et al, ).We found that, with the influence of STZ on the mGlu5 level of the model group, the expression of p‐NMDA2B presented the same downward trend, and the expression of NMDAR2B increased. Subsequently, SZL and donepezil also increased the expression of p‐NMDAR2B and decreased the NMDAR2B level in the drug treatment groups, among which the changes were most obvious in the SZL high‐dose group, while this effect was not obvious in the SZL low‐dose group (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…in a volume of 5 mL/kg body weight. The dose used for VU0360172 (30 mg/kg) was selected on the basis of our previous data [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…This method has a number of limitations, including the need to pool tissue from several animals, the need to perform ex vivo experiments in slices, and the lack of information on endogenous InsP levels (and, therefore, on the specific activity of 3 H-InsP). We have developed a new method for the in vivo assessment of mGlu5 receptor-mediated PI hydrolysis, based on systemic treatment with LiCl followed by the mGlu5 receptor PAM VU0360172 and determination of endogenous InsP levels by ELISA [ 31 ]. With the aid of this method, we have decided to study how mGlu5 receptor signaling is affected by spatial learning and by extinction in the dorsal and ventral hippocampus and in the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%